Evaluation of third molar agenesis associated with hypodontia and oligodontia in turkish pediatric patients - Gozde Seri̇ndere; Neslihan Ozveren; Meltem Tekbas Atay (Istanbul University, 2021)
Purpose: To evaluate the association between third molar (M3) agenesis and hypodontia and oligodontia in pediatric patients by using panoramic radiography. Materials and Methods: Panoramic radiographs of 1,471 patients (899 females; 572 males) and 5,884 teeth were retrospectively evaluated. The age and gender of the patients were recorded. Patients ages 9-15 years old were included in the study. The mean age was 12.76. The agenesis of M3 teeth and the relationship between M3 agenesis and hypodontia and oligodontia were recorded according to findings from the upper and lower jaw, in both the right and left locations, along with the number of M3 with agenesis. Data were analyzed using chi-square and McNemar tests (p<0.05). Results: A total of 1,319 (89.7%) patients had all M3 teeth present in the mouth, while the other 152 (10.3%) had congenital agenesis in one or more teeth. The number of teeth in which M3 agenesis was seen, in order of the number of missing teeth, was one (2.6%), two (2.4%), three (1.0%) and four (4.3%). Hypodontia was detected in 37 patients and oligodontia was detected in 3 patients. Conclusion: The prevalence of M3 agenesis varies from one population to another. One of the dental anomalies associated with M3 agenesis is hypodontia and oligodontia. In this study, M3 agenesis varied in terms of region and gender; hypodontia was also significantly higher in patients with missing mandibular M3.